Дослідження систем мобільного зв’язку нових поколінь на основі використання технології SDR - Бондаренко, І. М. (ХНУРЕ, 2023)
The object of research is the systems of mobile communication systems of GSM and LTE standards. The subject of research is models of GSM and LTE mobile communication systems implemented on the basis of SDR technology.The aim of the work is to create laboratory works on modelling and research of new generation mobile communication systems based on SDR technology for their use in the educational process in the specialty "Telecommunications and Radio Engineering". Methods of research: comparison, analysis, modeling.
Keywords: технології SDR; GSM